Pengaruh Gaya Kepemimpinan Transformasional, Sistem Pengendalian Internal, Budaya Organisasi dan Kecerdasan Emosional pada Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Sragen - Nisrina Luthfita Tsany; Fatchan Achyani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of Transformational Leadership Style, Internal Control System (SPI), Organizational Culture, and Emotional Intelligence on the Quality of Local Government Financial Reports in Sragen Regency. A quantitative approach was used with data analysis through Structural Equation Modeling-Partial Least Square (SEM-PLS). The sample consisted of SKPD employees in Sragen Regency, selected using purposive sampling. The results show that 81.3% of the variation in financial report quality can be explained by these factors. Transformational Leadership Style did not have a significant effect on financial report quality, while SPI, Organizational Culture, and Emotional Intelligence had a significant impact. Based on these findings, it is recommended that the local government focus on strengthening SPI, organizational culture, and improving employees' emotional intelligence to enhance the quality of local government financial reports.